TELAAH METODE “SUDUT PANDANG” DALAM NOVEL BERBAHASA INGGRIS MENURUT M.J. MURPHY - - Jaufillaili (Jurnal Tuturan, 2012)
Every novel is a story. And there are different ways of telling a story. Here, then, are some of the main ways of telling a story, in other word is viewpoint, as used in the novels. According to M.J. Murphy there are six viewpoints usually used in novels that will be discussed briefly one by one in the following article.